Jogo e protagonismo da criança na educação infantil - Lívia Carvalho de Assis; André da Silva Mello; Amarílio Ferreira Neto; Wagner dos Santos; Omar Schneider (Universidade do Minho, 2015)
In this article, it is analyzed how children appropriate and use playful activities (games) in a Children's Education Center located in the city of Vitória/ES/Brazil, in order to understand the role they establish in the relations with such cultural forms of expression. To do so, the Studies with the Daily Life were used as a methodological assumption. Data was produced through narratives and participant observations, for a four-month period of school insertion. The analyzes reveal that the game is lived by children in spontaneous situations and, above all, in Physical Education classes. In the first case, the children organize their own practices, predominantly of symbolic games; whereas in the classes, they act tactically, altering the games proposed by teachers according to their interests and needs. In both cases, Vygotsky social-historical perspective and Certeau's concept of productive consumption highlighted the cultural production of the children in the relations they establish with the game, denoting its main role.